The impact of internal marketing on customer satisfaction in the banking sector: A case of CRDB bank - Richard E. Ollotu (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master’s degree of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.